Motivasi Wanita Sebagai Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Agroindustri serta Kontribusinya Terhadap Pendapatan Keluarga di Kelurahan 29 Ilir Kota Palembang: - - Nadilla Oktarini; Elly Rosana (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2026)
Women fulfill not only the role of homemakers but also contribute significantly to the family economy, with many opting to work in Agro-Industrial Micro, Small and Medium Enterprises (MSMEs). This study aims to achieve the following objectives: (1) To assess the level of motivation among women as MSMEs enterpreneurs in Agro-Industry in the 29 Ilir Urban Village Palembang City. (2) To analyze the income of women working in Agro-Industrial MSMEs in the 29 Ilir Urban Village and their contribution to household income. (3) To analyze the relationship between work motivation and income for women in this sector. Conducted in July 2024, this research was situated in the 29 Ilir Urban Village Palembang City, utilizing a purposive sampling method for site selection. The study employed a survey methodology, with a Simple Random Sampling technique involving 30 women working in Agroindustrial MSMEs. Data collection comprised both primary and secondary data, with data analysis executed through Likert scale analysis and Spearman Rank correlation analysis. Findings reveal that the Existence, Relatedness, Growth (ERG) motivation of women in Agro-Industrial SMEs is rated high, with an average score of 3.02, indicating that their motivational needs are being met. The average monthly income for these women is Rp2,280,834, which remains below the Palembang Minimum Wage (UMK), with their contribution to family income at 60%, reflecting a moderate level of contribution. Furthermore, there exists a positive and significant relationship between work motivation and income among women employed in AgroIndustrial MSMEs in the 29 Ilir Urban Village Palembang City.